A Bibliometric Analysis of Scholarly Activity of Authors of Research Articles Published in the Journal of Physician Assistant Education from 2011-2020. Issue 4 (1st December 2022) - Bouton, Marcia; Halasy, Michael
Abstract : Introduction: The purpose of this study was to analyze bibliometric data and trends of author contributions to the Journal of Physician Assistant Education (JPAE) from 2011-2020. Methods: Author data were collected from JPAE research articles published from 2011-2020. Publication history and h-index were obtained from Scopus. Data collected included first authors, last authors, and PA authors as well as trends in publications in JPAE . Descriptive statistics, ANOVA, and Wilcoxon rank-sum tests were completed. Results: From 2011-2020, 200 research articles were published in JPAE; the volume was constant. Of 698 authors listed, 374 were physician assistants (PAs). Overall, contributing authors had a mean publication number of 19.6 (1-327) compared to 12.1 (1-163) for PAs. First and last PA authors had mean publication numbers of 13.2 and 16.1, respectively, and an average h-index of 3.2 and 4.4, respectively. The overall author h-index was 5.2. The mean number of publications for non-PA last authors was 32.9. Publication to h-index proportion was similar between PAs and other authors. The top 25 th percentile of PA authors published > 9 indexed documents, 3 times the number published by those in the 1-75 th percentile. Discussion: PA author articles in JPAE from 2011 to 2020 were fewer than those by non-PAs but were as likely to have a proportionate h-index. PAs listed as first and last author were highly published. Trends suggest that when PA first authors work with PA last authors, there may be a more egalitarian relationship, and mentorship patterns may also exist within these groups. Increasing publication numbers from 2011 to 2020 for PA first and last authors indicates increasing academic contribution.